Klasifikasi Relief dan Adaptasi Pola Permukiman Penduduk Dataran Tinggi di Kabupaten Ogan Komering Ulu Selatan (Universitas Negeri Semarang, 2022)
The objective of this study was to identify variations in relief morphologies in South OKU Regency, South Sumatra, utilizing elevation and slope characteristics. The subsequent objective is to determine the pattern of adaptation of residential settlements to the types of relief that exist in the highlands of South OKU Regency. Using reclassification of the 30' DEM SRTM imagery, the data analysis method used to determine the relief class. The findings of the reclassification are then overlaid and associated with the settlement pattern in the highlands using hot-spot analysis (Getis-Ord Gi*) in order to provide an understanding of the spatial adaption pattern of human settlements. The investigation revealed that the relief of plains was 34%, that of steep lowlands and hills was 9%, that of high altitude plains was 9%, that of plateaus was 22%, and that of mountains was 26%. According to the results of the overlay analysis, the majority of settlements are located on high altitude plains and low plateaus. Analysis by Getis-ord Gi* of 287 locations of settlement in the highlands revealed that 51 points exhibited a clustered pattern (hot spots), 170 points a random pattern, and 66 points a dispersed trend (cold spots). The clustering developed in the districts of Warkuk Ranau Selatan, Sungai Are, and Sindang Danau. Muaradua Kisam, Kisam Ilir, Kisam Tinggi, and Banding Agung are the districts where the settlement pattern tends to dispersed. The dominating terrain consists of sloping to plain slopes, which correlates with the pattern of dispersed settlements. The image indicates that the settlement pattern is more responsive to the parameters of slope and altitude than to the roughness of the relief.